THE BALI PROVINCIAL DPRD'S COMMISSION IV IMPLEMENTS ADAPTIVE GOVERNANCE IN RESPONSE TO EDUCATIONAL DISPARITIES IN REMOTE AREAS THROUGH THE CIPP MODEL - I Gede Bayu Mahardika; Ida Bagus Raka Suardana (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study aims to analyze the implementation of adaptive governance by Commission IV of the Bali Provincial DPRD in responding to educational disparities in remote areas using the CIPP (Context, Input, Process, Product) evaluation model. This research employs a descriptive qualitative approach, with data collected through in-depth interviews, field observations, and documentation. Informants were selected purposively based on their relevance to the research focus. The findings reveal that educational inequality in remote areas of Bali is a structural issue influenced by limited infrastructure, uneven distribution of resources, and socio-economic conditions. From the context aspect, there is a significant gap between ideal conditions and field realities. From the input aspect, resources are quantitatively adequate but not optimally distributed or utilized. In terms of process, policy implementation has shifted toward a more participatory and field-based approach, although it has not yet been systematically institutionalized. Meanwhile, from the product aspect, policies have produced initial impacts such as increased attention and educational assistance, but have not significantly reduced disparities. Overall, the implementation of adaptive governance remains in a transitional phase toward a more adaptive, responsive, and sustainable governance system.